Selective oxidation of colour-inducing constituents in raw sugar cane juice with potassium permanganate. (15th November 2019) - Fang, Yida; Ellis, Anderson; Uchimiya, Minori; Strathmann, Timothy J.
Highlights: Potassium permanganate is more effective for sugar decoloration than other oxidants. Oxidation of sugar colorants is more effective at ambient temperature than 70 °C. Sucrose, a key component in sugar, is not affected during permanganate treatment. Distinct kinetic stages were found for sugar colorants reaction with permanganate. Solid Mn product residuals can be effectually removed with alum coagulant. Abstract: Colour removal in raw sugar remains a crucial but expensive process in the sugar industry. In this report, permanganate (MnO4 − ) oxidation is explored as an alternative method to remove colour-inducing constituents in sugar cane juice/produced raw sugar. Experiments indicated alum, an inexpensive coagulant, was able to remove residual Mn species produced after MnO4 − treatment. The optimal dosages of MnO4 − and alum for decoloration of a 17 wt% raw sugar solution (70 °C) was found to be 4 mM and 2 g/l, respectively. Removal of colour and Mn removal were further improved at ambient temperature. Sucrose, the major component of raw sugar, was not affected during treatment with MnO4 − and alum. Two-phase kinetic behaviour for MnO4 − oxidation was observed, where an initial rapid oxidation phase is followed by a second slower reaction phase. These results suggest permanganate oxidation is a promising alternative for accomplishing the decoloration of raw sugar solutions.